LITERATURE REVIEW ON THE OVERVIEW OF RISK FACTORS OF SEVERE PREECLAMPSIA IN PREGNANT WOMEN - Solehati, Tetti; Andini, Melina Rike; Triesna, Meuthia Saulikha; Zaenal, Zabina Syaharani; Iqroansyah, Rifa Ikbal; Sakti, Dimas Wibawa; Kosasih, Cecep Eli (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2024)
Severe preeclampsia (PEB) is one of the causes of maternal death. Pregnant mothers must have adequate knowledge about dangerous risk factors during pregnancy, especially PEB, so that they can manage a safe pregnancy to prevent and minimize maternal or infant death. Objective: to identify risk factors for severe preeclampsia in pregnant women. Method: This research design uses a literature review by collecting articles from databases and search engines such as; PubMed, Garuda, Semantic Scholar, Neliti, and EBSCO use the keywords